Determination of repeatability and reproducibility of EBC accepted methods: V – Beer: Submitted on behalf of the Analysis Committee of the European Brewery Convention - Benard, M. (BrewingScience, 2000)
Methods published in Analytica-EBC for the determination of Beer Alcohol (9.2.1), Real, Apparent and Original Extracts (9.4), Real Degree of Fermentation (9.5), Colour (9.6), Final Attenuation (9.7), Bitterness (9.8), Total Nitrogen (9.9.1), Free Amino Nitrogen (9.10), Total Polyphenols (9.11), Vicinal Diketones (9.24.1), Total Carbohydrate (9.26) and Fermentable Carbohydrate (9.27) have been collaboratively tested by the European Brewery Convention Analysis Committee according to the ISO standard 5725. Repeatability (r₉₅) and reproducibility (R₉₅) values are presented.